MEMAHAMI FENOMENA CYBERBULLYING PADA SELEBGRAM DI MEDIA SOSIAL INSTAGRAM - Jihan Nur Firdausa Pasha Kristianti; Muhammad Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Globalization causes interactions from one person to another with coverage of all people in the world so that it seems as if there is no limit in obtaining various information from various parts of the world. However, with the ease of communication, it does not rule out the possibility of crime occurring in cyberspace. This is the background to the rise of cyberbullying cases against celebrities on Instagram. Cyberbullying is generally defined as an act of intimidation or verbal violence by perpetrators via the internet or social networks. This study aims to understand how celebrities experience the cyberbullying they experience, how celebrity views the cyberbullying they experience, and to find out what responses the celebrities give in responding to the cyberbullying they experience. In this study, the interpretive paradigm was used with a phenomenological approach using a qualitative descriptive analysis method, new media theory and stimulus-response model theory. Using a phenomenological approach, this study seeks to understand the phenomenon of cyberbullying through the perspective of the victim. The subjects of this study consisted of five informants by conducting in-depth interviews. The findings of this study are seen from the perspective of the celebrity as a victim. The conclusion is that the researchers found that the occurrence of cyberbullying was driven by the advancement of the internet. The act of cyberbullying experienced by celebrities as victims also affects the mentality of the victims themselves and is a scary scourge, but at the same time it can be something that is indirectly beneficial. In addition, the responses made by the victims were broadly the same, however, only a few people chose to hand over this case to the authorities.